Synucleins - Biochemistry and Role in Diseases 2020
DOI: 10.5772/intechopen.83647
|View full text |Cite
|
Sign up to set email alerts
|

Role of Osmolytes in Amyloidosis

Abstract: Osmolytes are naturally occurring small organic molecules present in all kingdoms of life. These organic molecules are accumulated by living systems to circumvent stress conditions. A number of human diseases have been grouped under the protein-misfolding diseases. These entire diseases share the same hallmarks of the presence of cellular inclusions and plaques that are deposited in the cells and tissues affected by the disease. These misfolded forms of protein are responsible for initiating toxic cascades in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 140 publications
0
8
0
Order By: Relevance
“…Osmolytes would be of immense significance for application in a large number of human diseases. Since osmolytes are accumulated under different disease conditions, identifying specific osmolytes concerning upregulation or downregulation in the cell under particular diseases will be useful for the selective use of osmolytes against the disease. , Osmolytes provide stability to the folded, functional shape of the protein and change the folding balance away from aggregation or protein degradation. They are often known as chemical chaperones.…”
Section: Discussionmentioning
confidence: 99%
“…Osmolytes would be of immense significance for application in a large number of human diseases. Since osmolytes are accumulated under different disease conditions, identifying specific osmolytes concerning upregulation or downregulation in the cell under particular diseases will be useful for the selective use of osmolytes against the disease. , Osmolytes provide stability to the folded, functional shape of the protein and change the folding balance away from aggregation or protein degradation. They are often known as chemical chaperones.…”
Section: Discussionmentioning
confidence: 99%
“…They observed that TMAO, sorbitol, and glycerol resulted in lowering the rate of fibril production by reducing the progression of the unfolding of monomers. The above-mentioned investigational results have indicated an excellent link through volume segregation principle relevant to polymer crowding [38].…”
Section: Osmolyte Prevents Protein Misfolding Aggregation and Fibrimentioning
confidence: 83%
“…The alteration in AQP2 (aquaporin-2) gene causes misfolding of AQP-2 protein that may lead to developing diabetes insipidus in mammals. However, as soon as osmolytes like glycerol (1M) were supplemented in the cell culture medium, glycerol re-established the folded arrangement and consequently the appropriate reshuffle of this protein in the cell [37,38].…”
Section: Osmolyte Prevents Protein Misfolding Aggregation and Fibrimentioning
confidence: 99%
“…Moreover, Ignatova et al have shown that since proline contains charged groups, it might induce electrostatic repulsion on interacting with a polypeptide chain at the start of protein aggregation . For example, proline at higher concentrations has been reported to encourage folding and inhibit aggregation of bovine carbonic anhydrase and lysozyme. , Among many osmolytes, trehalose, sorbitol, arginine, glycine-betaine, TMAO, and proline are industrially important osmolytes that prevent the protein misfolding from aggregation (Figure ). It has been found that trehalose, sorbitol, and arginine are effective excipients for the formulation and purification of therapeutic proteins. , Many neurological diseases are associated with the progressive accumulation of misfolded or aggregated proteins in the brain .…”
Section: Osmolytes As Efficient Protein Folders and Aggregation Modul...mentioning
confidence: 99%